Alcohol Use Disorders and an fMRI Stress Task: A Connectivity Analysis - (:unkn) unknown (My University, 2014)
Little research has been conducted on neuronal stress processing in individuals with alcohol dependence (AD). The present study examined neural stress response in AD individuals compared to controls using an fMRI stress task, assessing amygdala activation and its connectivity to the medial prefrontal cortex (mPFC). Further, the study analyzed the impact of hormone levels and subjective stress on frontal-limbic connectivity patterns. Ten abstinent AD individuals and 11 controls were recruited. Subjects participated in an fMRI stress task. A region of interest (amygdala) analysis was conducted using area-under-the-curve. This activation was then examined in a whole brain functional connectivity analysis. Follow-up analyses investigated whether brain activation could be predicted by cortisol, ACTH, and subjective stress. As hypothesized, the present study found increased amygdala activation in the AD group in comparison to controls, as well as decreased bilateral amygdala connectivity with the mPFC, as well as fronto-temporal and cerebellar regions. Hormone levels collected a year prior, but not subjective stress, predicted activation and connectivity.
Keywords: Alcohol Dependence; fMRI; Functional Connectivity; Stress; Stress Hormones